Optimizing nitrogen application strategies can improve grain yield by increasing dry matter translocation, promoting grain filling, and improving harvest indices - Li, Chuanliang; Shi, Yu; Yu, Zhenwen; Zhang, Yongli; Zhang, Zhen (Frontiers in Plant Science, 2025)
Nitrogen application enhances the grain yield of winter wheat by improving its physiological activity, dry matter production, and grain filling. However, reconciling nitrogen inputs using conservation irrigation remains challenging in water-limited wheat systems. A two-year field experiment was conducted during the 2020–2022 growing seasons with four nitrogen treatments (0 kg ha−1, N0; 150 kg ha−1, N150; 210 kg ha−1, N210; and 270 kg ha−1, N270). The responses of the senescence, dry matter accumulation and transfer, grain-filling, and grain yield of wheat to the nitrogen application rate were studied. The SPAD value, photosynthetic capacity, and antioxidant capacity of N210 flag leaves were not significantly different from those of N270 between 7–28 d after anthesis. However, these parameters were significantly higher in the N210 group than in the N0 and N150 groups. N210 and N270 significantly increased the sucrose content and sucrose phosphate synthase (SPS) activity in flag leaves relative to N0 and N150. Nitrogen application had a significant impact on dry matter transport within plants. Compared to N0, N150, and N270, dry matter transport in N210 wheat increased by 541.60–811.44 kg ha−1, 165.07–173.49 kg ha−1, and 179.02–216.74 kg ha−1, respectively, after anthesis. N210 significantly extended the active grain-filling period, leading to an increased grain weight. At maturity, the grain dry matter distribution in N210 was significantly higher than that in the other treatments, resulting in grain yield increases of 70.10%, 11.16%, and 6.81% compared to N0, N150, and N270, respectively. Therefore, under supplemental irrigation conditions in the North China Plain, moderate nitrogen reduction to 210 kg N ha−1 (N210) enhanced grain yield by delaying flag leaf senescence, improving dry matter remobilization, and optimizing grain-filling processes. The findings provide novel insights into the physiological mechanisms through which maintaining plant cellular physiological activity enhances crop productivity.